Strategic Plan for the Development of the RS Bersalin Grha Mutiara in 2019-2023: Policy Implementation - Syarahhandi, Melsha; Savitri, Mieke (Journal of Indonesian Health Policy and Administration, 2020)
This research discusses the Strategic Plan for the Development of the RS Bersalin Grha Mutiara in 2019-2023, using the theory of Strategic Planning to observe and evaluate external environmental opportunities and threats as well as the internal strengths and weaknesses of the hospital, to determine the right strategic plan. This study is a qualitative research using primary data, in-depth interviews with informants, observation and decision making with CDMG (Consensus Decision Making Group), and secondary data obtained from the BPS (Central Bureau of Statistics), Dinas Kesehatan Subang (District Health Office) Profile, Profile and Financial Report of RS Bersalin Grha Mutiara. From this study, the position of RS Bersalin Grha Mutiara, according to IE Matrix, is in Cell V (Hold and Maintain) and SWOT Matrix in Quadrant II (Internal Fixed It Quadrant). The matching stage resulted in a Product Development strategy, which, through the QSPM matrix, determine that the chosen strategy would be the development of HCU / NICU / PICU. This plan then elaborated in the implementation plan using the Balanced Scorecard.